The Effect of Childhood Infection on Hearing Function at Age 61 to 63 Years in the Newcastle Thousand Families Study. Issue 2 (March 2015) - Pearson, Fiona; Mann, Kay D.; Rees, Adrian; Davis, Adrian; Pearce, Mark S.
Abstract : Objectives: It is known that childhood hearing function can become impaired after the occurrence of specific infections. However, evidence on the effect of common childhood infections on adult hearing function is limited. The objective of the study was to identify whether associations exist between the occurrence of common childhood infections in a UK birth cohort and hearing function across different frequencies at age 61 to 63 years. Design: The Newcastle Thousand Families study is a birth cohort of all individuals born in May and June 1947 to mothers resident in Newcastle upon Tyne, United Kingdom. Of the original cohort members who had an audiometry test at age 61 to 63 years, 333 had data available on infections during their first year of life and 296 on infections up to their fifth year of life. These data were analyzed using linear regression in relation to adult hearing function across differing frequencies in isolation. Results: After adjustment for sex, overcrowding in the first year, having had an ear operation, and having worked in a loud environment, significant negative associations were identified between adult hearing and tonsillitis at 250 Hz ( p = 0.013), 1 kHz ( p = 0.018), 6 kHz ( p = 0.012), and 8 kHz ( p = 0.033); otorrhea at 4 kHz ( p = 0.005), 6 kHz ( p = 0.003), and 8 kHz ( p = 0.002); bronchitis (two or more episodes) at 2 kHz ( p = 0.001), 3 kHz ( p = 0.005), 4 kHz ( p = 0.009), 6 kHz ( p < 0.001), and 8 kHz ( p < 0.001); and the total number of severe respiratory infections in the first year at 2 kHz ( p = 0.037), 3 kHz ( p = 0.049), 4 kHz ( p = 0.030), 6 kHz ( p < 0.001), and 8 kHz ( p = 0.006). That is, individuals who had tonsillitis, bronchitis (twice or more), otorrhea, or a severe respiratory infection (twice or more) in their first year of life were more likely to have impaired adult hearing function than those who did not have any infections in early life. Conclusion: The occurrence of some, but not all, childhood infections appears to have an effect on adult hearing function across different frequencies. Reducing the incidence of infectious diseases in early life may reduce subsequent incidence of hearing impairment among adults. However, further research in modern cohorts is needed to clarify the links between infectious childhood diseases and adult hearing function. Abstract : Identifying preventable risk factors for adult hearing loss could inform interventions aimed at alleviating the burden of this disease. It is known that specific infections can impair childhood hearing function. However, evidence on common childhood infections, including those known to impair childhood hearing, and their effect on adult hearing is limited. This study found that individuals who had tonsillitis, otorrhea, or bronchitis during their first year, or a severe respiratory infection up to five years of age, were more likely to develop impaired hearing as adults across differing frequencies than individuals who had not.